Challenges of navigating brands through social media : marketing managers point of view - Marušić, Tajana (Array, 2021)
Creating and maintaining a successful brand has always been a longterm activity that required skills, knowledge, financial means and time. The success of global brands did not happen over time, and it seems that before social media there was always something precious that brand`s had – time. Time to communicate, time to create marketing campaigns, time to grow and evolve. Today, in the time of social media – there is everything but the time. Communication between consumers and brands is fast, global, and exposed for everyone to see and comment thanks to social media. Brands are more vulnerable than ever; consumers are in the position of power and now take an equal part in creating brands success. Brand management is changing, and marketing managers are faced with many challenges of navigating brands through social media. These challenges were the main idea behind the article. Explorative qualitative research was conducted by in-depth interviews of ten successful marketing managers in Croatia from various industries. From marketing agencies, food companies, the banking sector to the IT sector and direct TV sales, retail chain of sports shoes and equipment. In-depth interviews provided insight into their opinions based on experience in topics such as advantages and disadvantages of advertising on social media, measurement of advertising on social media, major challenges in brand management in a social networking environment; whether social networks and social media are synonymous or two different terms; what are the advantages and disadvantages of real-time consumer communication: and ultimately whether influencers are an indispensable variable in today"s advertising or just a passing trend.